Ekspozycja stoków wydm w Kotlinie Toruńskiej a wybrane elementy ekosystemu boru sosnowego – wstępne wyniki badań - Sewerniak, Piotr; Bednarek, Renata; Szymańska, Aneta (Leśne Prace Badawcze, 2011)
The characteristics of an old-growth (135 years old) Pinus sylvestris stand located in the Toruń Basin (central Poland) were compared on south- and north-facing dune slopes. The main variables compared were the microclimate (air temperature and relative air humidity), soil (morphology, intensity of the podzolization process, humidity, organic matter stock and total nitrogen stock) and phytocenosis (species composition and dry biomass of the ground vegetation, height and diameter at breast height of pines). The north-facing slope differed from the south-facing slope in several important ways: On the north-facing slope; (1) the mean annual air temperature was 0.5°C lower and relative air humidity 0.8% higher; (2) podzolization process was more intensive; (3) soil humidity was more than three times higher; (4) the organic horizon was thicker and stocks of soil organic matter greater (18.2 kg m -2 compared with 11.9 kg m -2 ); and (5) the total soil nitrogen stock was greater (302 g m -2 compared with 257 g m -2 ). These differences caused dissimilarities in phytocenosis (the plant community) between the opposing dune slopes. The species composition of the ground vegetation was significantly different between the slopes, due mainly to differences in the moss layer. The dry biomass of the ground vegetation on the north-facing slope was about twice that of the south-facing slope (138 g m -2 compared with 68 g m -2 ). Surprisingly, average pine height was lower on the north-facing slope in spite of its more-favourable moisture and trophic conditions compared with the south-facing slope. This suggests that light conditions among these dunes may affect pine growth more than soil moisture or trophic structure. The study indicates that at a local scale the slope exposure of a dune is an important factor increasing the pine ecosystem heterogeneity in the Toruń Basin.